2004
DOI: 10.1007/s00228-004-0761-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between concomitant use of several systemic NSAIDs and an excess risk of adverse drug reaction. A case/non-case study from the French Pharmacovigilance system database

Abstract: This study shows that concomitant use of two or more NSAIDs was associated with an excess risk of adverse effects such as hepatic injury, acute renal failure and gastrointestinal bleeding. Although simultaneous use of several systemic NSAIDs has no pharmacological justification, this may raise a serious public health problem with the increasing use of over-the-counter non-steroidal anti-inflammatory agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…This is in line with an analysis of 54,583 reports of suspected adverse drug reactions from the French Pharmacovigilance database that suggested a six- to sevenfold higher risk for severe ADRs (hepatic injury and acute renal failure) when two NSAIDs or more were administered at the same time [27]. In light of the well known and broad spectrum of adverse drug reactions related to NSAIDs the high number of cases with NSAID as co-medications is not surprising.…”
Section: Discussionsupporting
confidence: 79%
“…This is in line with an analysis of 54,583 reports of suspected adverse drug reactions from the French Pharmacovigilance database that suggested a six- to sevenfold higher risk for severe ADRs (hepatic injury and acute renal failure) when two NSAIDs or more were administered at the same time [27]. In light of the well known and broad spectrum of adverse drug reactions related to NSAIDs the high number of cases with NSAID as co-medications is not surprising.…”
Section: Discussionsupporting
confidence: 79%
“…Clinard et al found a dose–effect relationship between the number of NSAIDs used and some severe hepatic injuries (hepatitis, liver failure or cirrhosis). The adjusted odds ratio was 1.1 (0.9–1.4) when one NSAID was mentioned but increased to 2.2 (1.2–3.8) when more that two NSAIDs were associated [40].…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies indicate that antiplatelet and anticoagulant combinations, with concomitant use of non-steroidal anti-inflammatory drugs (NSAIDs), selective serotonin re-uptake inhibitors (SSRIs) or antibacterial drugs increase bleeding risk [11,[13][14][15][16][17]. Up to 80% of anticoagulant users are described as using potentially hazardous combinations of medicines [18,19].…”
Section: Introductionmentioning
confidence: 99%